KEMAMPUAN BERARGUMENTASI SISWA MENGGUNAKAN MODEL TOULMIN PADA MATERI HUKUM NEWTON DI SMP NEGERI 57 PALEMBANG - Nely Andriani; Lucy Triananda; Supardi Supardi; Saparini Saparini; Evelina Astra Patriot (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2023)
This study aims to analyze the argumentation abilities of students in class VIII-1 in the odd semester of the 2022/2023 academic year at SMP Negeri 57 Palembang in the material of style and motion using the Toulmin's Argumentation Pattern (TAP) model. The Toulmin argumentation model is an instrument used to process arguments presented by students which consists of 6 indicators namely Claim, Data, Warrant, Backing, Qualifier, and Rebuttal. The method used in this research is descriptive research with a quantitative approach. The data collection technique was carried out in two stages, namely tests in the form of description questions and non-tests in the form of interviews with subject teachers. The results of the test research show that the level of students' argumentation abilities is low, where they are only at level 1 with a percentage of 58.10%, level 2 with a percentage of 30.95%, and level 3 with a percentage of 10.95% but no one is at level 4 yet and level 5. These results indicate that argumentation skills are still in the low category. The research results obtained that students have not been able to connect between material and concepts correctly. Then, learning activities carried out for some time were constrained by adjustments to the end of PPKM which had lasted for 3 years. Students are still adapting to the learning process that has begun to be carried out face-to-face. A teacher expected to be able to immediately provide the right learning process with the existing conditions